Coercivity enhancement of a Nd–Fe–B sintered magnet by diffusion of Nd70Cu30 alloy under pressure. (October 2015) - Chen, Fugang; Zhang, Tieqiao; Wang, Jing; Zhang, Lanting; Zhou, Gaofeng
Graphical abstract: Abstract : Application of pressure during grain boundary diffusion process (GBDP) using Nd70 Cu30 eutectic alloy enhances the coercivity greatly from 1367 kA/m in the annealed state to 1660 kA/m. The uniformity of coercivity distribution was improved due to the large effective diffusion depth under pressure. Continuous grain boundary phase was observed both on the surface and in the center of the magnet after GBDP under pressure. Mechanism of coercivity enhancement due to micro cracks is discussed based on the observation.